2016
DOI: 10.5892/ruvrd.v14i2.2695
|View full text |Cite
|
Sign up to set email alerts
|

Importância Do Programa Hiperdia Na Adesão Ao Tratamento Medicamentoso E Dietetico Em Uma Unidade De Saúde Da Família (Usf)

Abstract: IMPORTANCIA DEL PROGRAMA HIPERDIA A ADHESIÓN DEL TRATAMIENTO MÉDICO Y DIETETICO EN UNA UNIDAD DE SALUD FAMILIAR (USF) RESUMENObjetivo: Analizar la importancia del Programa HIPERDIA el la adhesión a lo tratamiento medicamentoso y dietético en una Unidad de Salud de la Familia. Metodos: Se trata de un estudio exploratorio de carater descriptivo y cuantitativo desarrollado en una Unidad de Salud de la Familia de lo municipio de Campina Grande/PB, en 2014. La amuestra fue constituida por 106 usuarios registrados e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
0
0
4
Order By: Relevance
“…In continuity, it is observed that men with higher education and women with less education have a prevalence of acquiring the reduced disease when compared to the illiterate. Thus, regarding the level of education, the data are similar to the research carried out in a Family Health Unit in Campina Grande, Brazil, where a significant number of hypertensive users (61.2%) with up to five years of schooling were observed, in addition to the fact that the low level of education of the elderly represents high levels of vulnerability to other diseases and infections 13 .…”
Section: Discussionsupporting
confidence: 75%
“…In continuity, it is observed that men with higher education and women with less education have a prevalence of acquiring the reduced disease when compared to the illiterate. Thus, regarding the level of education, the data are similar to the research carried out in a Family Health Unit in Campina Grande, Brazil, where a significant number of hypertensive users (61.2%) with up to five years of schooling were observed, in addition to the fact that the low level of education of the elderly represents high levels of vulnerability to other diseases and infections 13 .…”
Section: Discussionsupporting
confidence: 75%
“…O vínculo fragilizado de diabéticos e hipertensos nas unidades investigadas foi notório, sendo restrita a busca por atendimento médico essencialmente para renovação de receitas de medicamentos, corroborando com os resultados encontrados em uma Unidade de APS na Paraíba, na qual 68% dos usuários procuravam o serviço somente para buscar a medicação de rotina, além disso, apenas 7,3% dos usuários do Programa HiperDia realizaram 2 ou 3 atendimentos ao ano para consultas com os profissionais. Concomitantemente, cerca de 46,6 % dos usuários acompanhados pelo mesmo programa na Bahia não compareciam a UBS há seis meses ou mais para o acompanhamento da(s) patologia(s) 17,18 .…”
Section: Discussionunclassified
“…Os dados apontaram a importância do programa HIPERDIA, tendo em vista que este pode identificar as dificuldades que os usuários hipertensos e/ou diabéticos da ESF possuem em relação à adesão aos tratamentos, sendo a dificuldade mais prevalente a realização de uma dieta alimentar adequada. Sabe-se da necessidade de um acompanhamento mensal para esses usuários, conscientizando-os sobre as mudanças no estilo de vida, para prevenir essas patologias, e a importância na adesão aos tratamentos propostos para que possuam uma melhor QV e evitem o aparecimento de complicações 27 .…”
Section: Influência Da Prática De Atividade Física Sobre a Qv De Pessunclassified